RECREATIONAL GAMES AS A CATALYST FOR BETTER AGING: A SIX-WEEK INTERVENTION ON QUALITY OF LIFE AND HEALTH IN OLDER ADULTS - Nagesh; Kanojiya, Rahul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this study was to evaluate the impact of a six-week recreational games training program on the quality of life, lung capacity, and flexibility of older adults aged 60 to 79 years residing in Gwalior city. The study included ten participants who were evaluated using the Sit and Reach Test for flexibility, a dry spirometer for lung capacity, and the OPQOL-35 questionnaire to assess their quality of life. Data were collected both before and after the intervention to measure the effects of the program. The intervention consisted of structured recreational activities designed to engage the participants physically, socially, and mentally. The results demonstrated significant improvements in the participants' overall quality of life and lung capacity, as evidenced by higher post-test scores. Enhanced physical well-being, reflected in better flexibility and increased lung capacity, was accompanied by improvements in emotional and social aspects of life, as reported in the OPQOL-35 responses. Statistical analysis revealed highly significant differences (p < .05) between pre- and post-test measures, confirming the positive effects of the intervention. These findings highlight the potential of recreational games as a practical and enjoyable approach to improving physical health, emotional well-being, and overall quality of life in older adults. Moreover, the study suggests that incorporating recreational activities into regular routines can serve as an effective strategy to promote healthy aging and prevent age-related declines in physical and mental health. By engaging older adults in meaningful and enjoyable activities, recreational games not only improve physical fitness but also foster social interaction and emotional support, contributing to a holistic approach to healthy aging. These results encourage further research and implementation of similar programs to benefit older populations in other communities.